PENGARUH CITA RASA, HARGA, DAN LOKASI TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA LESEHAN IKAN BAKAR CAK GABRIL DI SITUBONDO - Utari, Melgi Puji; Sari, Lita Permata; Minullah, Minullah (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
Marketing is an interconnected activity between companies and consumers as a system to generate profits, for this reason the right marketing strategy can increase the attractiveness of culinary destinations through Taste, Price, and Location, Customer satisfaction and culinary consumer loyalty in Situbondo Regency. The purpose of this study was to analyze and test the effect of Taste, Price, and Location in determining consumer loyalty with consumer satisfaction as an intervening variable. The population in the study were consumers of Lesehan Ikan Bakar Cak Gabril in Situbondo Regency. The sampling method is determined by probability sampling. Data analysis and hypothesis testing in research using the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application, show that Taste has a significant positive effect on customer satisfaction, Price has a positive but insignificant effect on customer satisfaction, Location has a significant positive effect on customer satisfaction, Taste has a significant positive effect on customer loyalty, Price has a positive but insignificant effect on customer loyalty, Location has a significant positive effect on customer loyalty, Customer satisfaction has a significant positive effect on customer loyalty. The results of the indirect effect hypothesis show that the variable Taste to consumer loyalty through customer satisfaction has a positive but insignificant effect, Price to consumer loyalty through customer satisfaction has a positive but insignificant effect, Location to consumer loyalty through customer satisfaction has a significant positive effect.